2022
DOI: 10.1111/jog.15533
|View full text |Cite
|
Sign up to set email alerts
|

The utility of systemic immune‐inflammation index and systemic immune‐response index in the prediction of adverse outcomes in pregnant women with coronavirus disease 2019: Analysis of 2649 cases

Abstract: Aim To investigate the association of systemic immune‐inflammation index (SII) and systemic immune‐response index (SIRI) with adverse perinatal outcomes in pregnant women with coronavirus disease 2019 (COVID‐19). Methods The cases were divided into (1) the Mild–moderate COVID‐19 group (n = 2437) and (2) the Severe–critical COVID‐19 group (n = 212). Clinical characteristics, perinatal outcomes, SII (neutrophilXplatelet/lymphocyte), and SIRI (neutrophilXmonocyte/lymphocyte) were compared between the groups. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
1
10
0
1
Order By: Relevance
“… 12 Similar to APACHI scores, one study used systemic immune-inflammation index (SII) and systemic immune-response index (SIRI) to study the adverse perinatal outcomes in pregnant women with (COVID-19). 13 The study found that both indicators might be used in combination with other clinical findings in the prediction of poor perinatal outcomes including pregnancy complications, NICU admission, and maternal mortality. Moreover, severe COVID-19 cases were shown to have significantly higher rates of inflammatory markers.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 12 Similar to APACHI scores, one study used systemic immune-inflammation index (SII) and systemic immune-response index (SIRI) to study the adverse perinatal outcomes in pregnant women with (COVID-19). 13 The study found that both indicators might be used in combination with other clinical findings in the prediction of poor perinatal outcomes including pregnancy complications, NICU admission, and maternal mortality. Moreover, severe COVID-19 cases were shown to have significantly higher rates of inflammatory markers.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, severe COVID-19 cases were shown to have significantly higher rates of inflammatory markers. 13 …”
Section: Discussionmentioning
confidence: 99%
“…No grupo 1 a idade média materna com desvio padrão era de 28,90 anos e (n=409; 16,8%) tinham idade materna avançada (≥35 anos), (n=27; 1,1%) possuíam HAS, (n=38; 1,6%) asma, (n=21; 0,8) diabetes melittus pré-gestacional e (n=587; 24,1%) apresentaram complicações no período gravídico. No grupo 2 a idade materna média com desvio padrão era de 30,45 anos, (n=58; 27,3%) tinham idade materna avançada, (n=32; 15,1%) eram hipertensas, (n=12; 5,6%) eram asmáticas, (n=11; 5,2%) possuíam diabetes mellitus pré gestacional e (n=190; 89,6%) tiveram complicações na gravidez 18 . Saúde Meio Ambient.…”
Section: Variáveisunclassified
“…Accumulating evidence has indicated that pregnant women infected with SARS-CoV-2 usually presents as asymptomatic or mildly symptomatic [ 7 , 8 ], and the clinical course of SARS-CoV-2 infected pregnant women is similar to that of the general population [ 9 ] with low morbidity and mortality rates [ 10 ]. In contrast, conflicting results reporting that infection of COVID-19 during pregnancy may result in a higher risk of obstetric complications and adverse perinatal outcomes [ 11 , 12 ], with significantly higher rates of pregnancy complications were observed in the severe-critical COVID-19 pregnant women [ 13 ]. Furthermore, most of the published data related to COVID-19 and pregnancy come from the analysis of small electronic health records and generally include only third-trimester pregnancies.…”
Section: Introductionmentioning
confidence: 99%